Study experience of using plant materials infected by fungi as substrate for microbial fuel cell - Kucherov, A. I.; Nechyporuk, O. Y.; Paliienko, K. O.; Savchenko, H. K.; Tymoshenko, L. S.; Yuzvenko, Y. V.; Drazhnikova, A. V. (Problems of Environmental Biotechnology, 2016)
Article presents the results of experimental investigation applicability of plant fallen materials contaminated by powdery mildew fungus E. flexuosa as substrate in microbial fuel cell (MFC). MCFs were presented in form of Winogradsky’s column. The measurements of generated voltage were carried out in MFCs with different composition during 5 weeks.